2024
DOI: 10.3389/fpsyg.2024.1322781
|View full text |Cite
|
Sign up to set email alerts
|

Ascribing consciousness to artificial intelligence: human-AI interaction and its carry-over effects on human-human interaction

Rose E. Guingrich,
Michael S. A. Graziano

Abstract: The question of whether artificial intelligence (AI) can be considered conscious and therefore should be evaluated through a moral lens has surfaced in recent years. In this paper, we argue that whether AI is conscious is less of a concern than the fact that AI can be considered conscious by users during human-AI interaction, because this ascription of consciousness can lead to carry-over effects on human-human interaction. When AI is viewed as conscious like a human, then how people treat AI appears to carry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 142 publications
1
5
0
Order By: Relevance
“…Conversely, an AI system that serves as a therapist (see above) models respectful and empathetic behavior can serve as a positive influence on users' interactions with others. Therefore, in line with Gambino et al [24], we argue that the requirements of the AI do not only influence our communication style and behavior towards the AI itself [31,32] but also towards other people when certain communication styles and behaviors are practiced and internalized (see also [3])…”
Section: Social Learning Theorysupporting
confidence: 82%
See 3 more Smart Citations
“…Conversely, an AI system that serves as a therapist (see above) models respectful and empathetic behavior can serve as a positive influence on users' interactions with others. Therefore, in line with Gambino et al [24], we argue that the requirements of the AI do not only influence our communication style and behavior towards the AI itself [31,32] but also towards other people when certain communication styles and behaviors are practiced and internalized (see also [3])…”
Section: Social Learning Theorysupporting
confidence: 82%
“…In addition, Gambino et al [8] noted the possibility of a reserved effect, whereby interactions with social agents may shape ensuing human-human interactions. This is supported by recent work by Guingrich and Graziano, who argue that schema activation may lead persons to ascribe consciousness to AI systems, which in turn affects the way other humans are treated [3]. Given these developments, it becomes crucial to 2 examine how AI influences our daily lives and relationships, particularly concerning text-and speech-based output irrespective of underlying technical complexities.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Results from studies on mind perception and attitudes toward AI can be contradictory, however. Some studies indicated that perceiving mind in AI related to acceptance of AI, whereas others suggested that it related to fear or discomfort [46][47][48][49][50][51]. The extent to which someone perceives AI as having a mind may be particularly related to the personality of the individual, rather than to the features of the AI agent in the study.…”
Section: Introductionmentioning
confidence: 99%